Biodegradation of dinitrotoluene by Pseudomonas PR7 in a fluidized bed bioreactor - Whitty, Katherine Keesling, author; Reardon, Kenneth F., advisor; Murphy, Vincent G., committee member; Linden, James C., committee member (Colorado State University. Libraries, 1997)
2,4-Dinitrotoluene (DNT) has been listed as a priority pollutant by the U. S. EPA. It is a waste product in the production of 2,4,6- trinitrotoluene (TNT) and toluene diisocyanate. Pseudomonas PR7 is able to completely degrade DNT via an oxidative pathway. Batch suspended-cell experiments were performed in order to determine the maximum specific growth rate Pmax/ and the Monod half-saturation constant. Ks. Parameter values of μmax = 0.1 h-1 and Ks = 14 mg/L were obtained by fitting experimental data to the Monod model. Immobilized-cell experiments in a fluidized-bed bioreactor (FBB) were performed in order to determine volumetric DNT degradation rate v for the biodegradation of DNT. A fluidized-bed bioreactor was chosen for study because (1) immobilization of cells onto particles allows for greater cell retention, and (2) fluidization of particles allows for mixing within the reactor. Greater cell retention allows for higher flow rates of liquid through the reactor and adequate mixing can alleviate the problem of low oxygen availability and other accumulation or depletion problems which occur in packed beds. Fluidization of immobilized cells in the FBB was achieved by the upflow of air and liquid. Data from residence time distribution (RTD) analysis of the FBB suggests that it behaves as a stirred tank reactor with small plug-flow regions and dead zones. The fluidized-bed bioreactor performance was compared with that of suspended-cell experiments and packed-bed experiments through direct comparison of DNT loading versus degradation rates. It was found that the fluidized-bed bioreactor performed as well as a previously reported system consisting of a packed-bed column in series with a stirred-tank reactor in one experiment using diatomaceous earth particles as the immobilization medium. The FBB did not perform as well as the packed-bed system in subsequent experiments using polycarbonate particles.
Keywords: Nitroaromatic compounds; Biodegradation